Avaliação do uso de ácido salicílico em germinação de sementes de pimentão - Basílio, Scarlet de Aguiar (2020)
Beel pepper participates in a significant part of the Brazilian fresh oler market, being among the ten most important vegetables in terms of economic value, being cultivated in all states of Brazil, with a planted area of approximately 13 thousand hectares and an estimated production of 290 thousand tons of fruit. Techniques that induce improvement in the physiological quality of the seeds are important to increase their performance and the uniformity of the plants in field conditions. The use of growth regulators can favor the performance of seedlings, speeding up the emergence of seeds of several species. Salicylic acid is a phenolic compound that is involved in a number of physiological processes, and has been considered as part of a new class of plant growth substances in addition to plant hormones. The aim of the following work was to evaluate the influence of salicylic acid on the germination and vigour of bell pepper (Capsicum annuun) seeds. The work was conducted in a laboratory at Universidade Estadual de Goiás- Campus Ipameri. The experimental design used was entirely randomized, arranged in a 3 x 5 factor scheme (3 lots and 5 doses) with 4 repetitions. Three lots of bell pepper cv seeds were used. Hard Cascadura Ikeda and All Big cv. The doses of salicylic acid were used in concentrations of 0.00g, 0.010g, 0.015g, 0.020g and 0.025g diluted in 100 ml of distilled water. The treatments were characterised by soaking the seeds in salicylic acid solution for eight hours. The following evaluations were performed for each cultivar: weight of 1000 seeds, germination speed index, first germination count, total germination, electrical conductivity, aerial and radicle length, dry mass of aerial and radicle and accelerated aging. The application of salicylic acid positively influenced the treatment of sweet pepper seeds cv. Cascadura Ikeda providing increased germination, increased germination at the first count, provided an increase in root length, thus, with the best result obtained in the concentration of 0.015 g. For cv. All Big at a concentration of 0.017g salicylic acid increased the rate of germination speed, total germination and shoot length